MONARCH Inventory for Causal Attribution in Homeopathy Case Reports: Explanation and Elaboration - Lamba, Chetna Deep; Mahajan, Nidhi; Gupta, Vishwa Kumar; Rutten, Lex; Teut, Michael; Tapakis, Lefteris; Hoover, Todd; Gerstenhoefer, Anna; Fok, Yuen Ying Yvonne; Manchanda, Rajkumar; van Haselen, Robbert (Homeopathy, 2024)
Background The Modified Naranjo Criteria for Homeopathy (MONARCH) inventory is a novel and useful tool for assessing the likelihood of a causal relationship between the homeopathic intervention and the ultimate clinical outcome.Objectives To explain and elaborate on the use of the MONARCH inventory to improve its consistency of use and thereby elevate the overall quality and evidentiary value of homeopathy case reports.Explanation and Elaboration Each of the 10 MONARCH inventory domains is explained and elaborated with the aid of references from published literature and hypothetical clinical situations. The MONARCH total score can range from −6 to +13; within that range, an arithmetic total of +6 is available from the scores of four critical domains, which should be given prominence in the overall consideration of causality. In reporting a clinical case, great importance should be placed on the narrative of the MONARCH evaluation process, domain by domain.Conclusion The application of MONARCH allows us to evaluate the likelihood of a causal relationship between the intervention and the observed clinical outcomes in successfully treated cases, thereby augmenting their evidentiary value.
Keywords: MONARCH inventory; causal relationship; homeopathic intervention; clinical outcome; case reports